2019
DOI: 10.1111/mcn.12856
|View full text |Cite
|
Sign up to set email alerts
|

Inadequacy of nutrients and contaminants found in porridge‐type complementary foods in Rwanda

Abstract: Child malnutrition remains persistently high in Rwanda. Complementary foods play a key role in young child nutrition. This study explores the quality and safety of complementary food products available in the Rwandan market. Ten of the most consumed porridge-type complementary food products in Rwanda have been analysed. Mean values of macronutrient and micronutrient contents were compared against three international standards and evaluated against label claims. Mean mycotoxin, microbiological, and pesticide co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…This result underscores the use of the dietary diversity as a better proxy of feeding practices and suggests that interventions to diversify children's diet have potential to improve child nutritional status of young children in Rwanda. However, studies found that complementary foods in Rwanda may be source of mycotoxins (56,57) . Consumption of mycotoxins, particularly aflatoxins, through complementary foods was found to be associated with child stunting in children (9-60 months) (58) .…”
Section: Discussionmentioning
confidence: 99%
“…This result underscores the use of the dietary diversity as a better proxy of feeding practices and suggests that interventions to diversify children's diet have potential to improve child nutritional status of young children in Rwanda. However, studies found that complementary foods in Rwanda may be source of mycotoxins (56,57) . Consumption of mycotoxins, particularly aflatoxins, through complementary foods was found to be associated with child stunting in children (9-60 months) (58) .…”
Section: Discussionmentioning
confidence: 99%
“…In particular, products were low in fat, iron, calcium, zinc, and phosphorus, but high in crude fiber, carbohydrates and magnesium (Mosha, Laswai, and Tetens 2000). Most recently, a study of CPCs in Rwanda found low and variable nutrient composition as well as high aflatoxin contamination (Grosshagauer et al 2019).…”
Section: Standards Quality Assurance and Asymmetric Informationmentioning
confidence: 99%
“…For example, iron deficiency anemia leads to cognitive impairment, increased risk of child and maternal morbidity and mortality, and low productivity at work [ 2 ]. Evidence suggests that these deficiencies can be partly attributed to inadequate intake of dietary micronutrients due to diets that are inadequate in terms of vitamin A, calcium, and iron [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%